The Relationship between Maternal and Neonatal Diseases and Retinopathy of Prematurity and Its Progression - M Haghshenas Mojaveri (Babol University of Medical Sciences, 2021)
BACKGROUND AND OBJECTIVE: Retinopathy of Prematurity (ROP) is a vasoproliferative retinal disease in preterm infants that can lead to disorders and blindness throughout life if not diagnosed and treated at an early age. Therefore, this study was performed to investigate the relationship between retinopathy of prematurity and various maternal and neonatal diseases. METHODS: This case-control study was performed on 828 premature infants (303 infants with ROP and 525 infants without ROP as controls) born in Ayatollah Rouhani Hospital, Babol, Iran, in 2009-2019. All medical information about maternal and neonatal diseases was collected from patient files. Preliminary eye examinations and follow-up were performed based on the local ROP treatment and follow-up guide to diagnose the stage and zone of ROP. Then, neonates were compared based on retinopathy and lack of infection in both groups in terms of maternal and neonatal diseases including congenital heart defect, premature rupture of membranes, anemia, urinary tract infection, hypertension, sepsis, transient tachypnea of the newborn, respiratory distress syndrome, gestational diabetes and preeclampsia. FINDINGS: Out of 828 evaluated neonates, 303 had ROP, including infants with preeclampsia (odds ratio of 2.54, p<0.001), infants with respiratory distress syndrome (odds ratio of 2.2, p<0.001) and infants with congenital heart defects (odds ratio of 1.53, p=0.047) had a higher chance of developing ROP. Moreover, infants with transient tachypnea of the newborn (odds ratio of 0.7, p<0.001) and infants with anemia (odds ratio of 0.373, p<0.001) had a lower chance of developing ROP. CONCLUSION: The results of the study showed that maternal preeclampsia, respiratory distress syndrome and congenital heart defects are among the diseases affecting the incidence of ROP.